Fructosyltransferase and inulinase production by indigenous coprophilous fungi for the biocatalytic conversion of sucrose and inulin into oligosaccharides. (November 2020) - Ojwach, Jeff; Kumar, Ajit; Mutanda, Taurai; Mukaratirwa, Samson
Abstract: There is a great interest in prebiotics consumptions eminence by their health promoting properties and economic market value. Filamentous fungi have been implicated as the key producers of fructosyltransferase (Ftase) and inulinase for synthesis of fructooligosaccharides (FOSs), which is used as a bioactive ingredient in functional foods. In this study, sixty-one indigenous coprophilous fungal strains were isolated, purified to monoculture and investigated for their potential use in biotransformation of sucrose and inulin into fructooligosaccharides (FOSs) and inulooligosaccharides (IOSs) by producing Ftase and inulinase enzymes, respectively. The molecular identification by 18S rDNA sequencing and morpho-taxonomic keys revealed that axenic fungal strains belonged to the genera Aspergillus, Neocosmospora, Trichoderma, Mucor and Fusarium . The crude enzyme extract from the isolates showed hydrolysis zones of 15–30 mm on the 2, 3, 5-triphenyltetrazolium chloride (TTC) and Lugol's iodine solution assay plates confirming the Ftase and inulinase activities, respectively. The submerged culture filtrates of eight fungal isolates showed high Ftase activity while six different fungal isolates exhibited high inulinase activity. The reaction products analysed with thin-layer chromatography and high-performance liquid chromatography coupled with refractive index detection indicated the presence of FOSs and IOSs. The strains isolated in this study have potential biotechnological implications to produce FOSs and IOSs. Graphical abstract: Image 1 Highlights: Here, sixty-one indigenous coprophilous fungal strains were isolated and purified. The isolates were purified to monoculture and identified by 18S rDNA sequencing. Identified as genera Neocosmospora, Trichoderma, Aspergillus, Mucor and Fusarium. Fungi were able to produce Ftase and inulinase for synthesis of oligosaccharides. TLC and HPLC analysis revealed isolates produced short-chain FOSs GF3, GF4 and GF5 .